Glucocorticoids and medroxyprogesterone acetate synergize with inflammatory stimuli to selectively upregulate CCL20 transcription. (1st March 2023) - Moliki, Johnson M.; Nhundu, Tawanda J.; Maritz, Leo; Avenant, Chanel; Hapgood, Janet P.
Abstract: The pro-inflammatory cytokine, chemokine (C-C motif) ligand 20 (CCL20), is emerging as a therapeutic target for immune-based therapies. Cooperative regulation of CCL20 by glucocorticoids and progestins used in endocrine therapy and pro-inflammatory mediators could modulate immune function and affect disease outcomes. We show that glucocorticoids as well as medroxyprogesterone acetate (MPA), the progestin widely used in injectable contraception in sub-Saharan Africa, cooperate with pro-inflammatory mediators to upregulate CCL20 protein and/or mRNA in human peripheral blood mononuclear cells (PBMCs) and human cervical cell lines. Changes in CCL20 mRNA levels were shown to be synergistic, as assessed by Chou analysis, cell- and gene-specific and to involve transcriptional regulation, with a requirement for a nuclear factor kappa B (NF-κB) site and glucocorticoid receptor (GR) involvement. The novel results suggest a mechanism whereby MPA, like glucocorticoids, may impact inflammation both systemically and in the genital tract in patients using MPA and/or glucocorticoid therapy. Highlights: Synergism between glucocorticoids (GCs) and TNFα may amplify inflammation. MPA like GCs but not NET synergizes with TNFα to upregulate CCL20 expression. The synergy is cell- and gene-specific, and requires both the GR and NFκB. MPA and NET may differentially affect HIV-1 pathogenesis and cancer prognosis.